Sistem Pendukung Keputusan Pemberian Kredit Menggunakan Metode Simple Additive Weighting (SAW) (Studi Kasus Koperasi Bengkawas Jaya) - Kiki Yasdomi, Detri Amelia Chandra (RJOCS (Riau Journal of Computer Science), 2017)
Cooperative Bengkawas Jaya is one of the businesses in the service sector savings and loans that have increased the number of customers each month causing increased amount of customer data management. In the process of Cooperative Bengkawas Jaya calculation of the value of customer data that will accept credit loan is done manually and frequent errors, so that the process of ranking the value would be inefficient and requires a long time. Therefore necessary a Decision Support System Loan Method Using Simple Additive Weighting (SAW) to solve the problem. Decision Support System Loans in this study built using the PHP programming language supported by MySQL database. The purpose and benefits of design analysis and decision support system that produces decision support system that can help Web basis of employee performance in the elections Jaya Cooperative Bengkawas customers who receive credit.